Structure of economics a mathematical analysis - Silberberg Eugene; Suen Wing (New York McGraw-Hill, 2000)
This text combines mathematical economics with microeconomic theory and can be required or recommended as part of a course in graduate microeconomic theory, advanced undergraduate or graduate-level mathematical economics, or any advanced topics course. I
Keywords: Mathematical economics